The development of the anxiety concentration index detection (AnCID) device for sports application enhance with IoT technology - Wan Nurlisa, Wan Ahmad; Mohd Azrul Hisham, Mohd Adib; Jaivitthiran, Jayakumar; Kusan, Reveendran; Muhammad Faiz, Mat Zuki; Ahmad Azfar, Mohammad Asmara; Ahmad Azri Syazwan, Mohd Sabri (AIP Publishing, 2023)
The paper presented an early development of an anxiety concentration index detection (AnCID) device for real-time anxiety measurements in individual sportspersons. Sports performance is interdependent with how the athlete perceives their anxiety level. The varying anxiety level will turn debilitative at specific points and result in poor performance, especially during the tournament. In addition, developing this digital AnCID device can help monitor the anxiety level according to the prescribed index. Detection refers to the physiological signals of the user. The proposed AnCID evaluated physiological sensing in detecting anxiety by integrating ESP8266 microprocessor sensors as a microcontroller. An appropriate Internet of Things (IoT) architecture for easier obtained measurement data from anxiety parameters and prepared a precise miniature electronic PCB board that can easily be attached to the human body. The anxiety data are classified into ranges, the data simultaneously transferred via Bluetooth HC-05, and the result is displayed on an LCD screen series. Further development, all the sensor’s data integrated well with smart devices, allowing multiple electronic devices with numerous capabilities to communicate for data exchange. This technological application is known as the Internet of Everything (IoE).